Simulation Approach for Soft Manipulators in Gazebo using Kinematic Model - Mendes, João Vitor S.; Matos, Victor S.; Novaes, Luis Victor S. C.; Silva, Lucas C. Da (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
Simulation of soft manipulators is a significant challenge for current robotics simulators due to the non-linear characteristics of their material, high number of degrees of freedom, and body flexibility. While the main efforts in this area have been concentrated on simulators using finite element modeling or dynamic model representations, this tool is limited to simulations in isolated environments. This article proposes a way to simulate soft manipulators by using a mathematical model for position estimation and a Bezier curve approximation for curvature estimation in Gazebo, a popular simulation tool in Robotics. The approach provides a framework for developing simulations of soft manipulators that can mimic the behavior of real manipulators in various environments that use URDF.